PERCEPTIONS ON QUALITY OF LIFE IN MALAYSIA: THE URBAN-RURAL DIVIDE - Hassan, Norhaslina; Mohd Jaafar, Noor Ismawati; Raja Ariffin, Raja Noriza; Abu Samah, Asmarulkhadi; Jaafar, Mohd Nazari (PLANNING MALAYSIA, 2013)
Spatial strategy then known as regional planning, was conceptualized and formally institutionalized in the Second Malaysia Plan, to be among the major instruments of the New Economic Policy (NEP). Urbanization in this context was envisaged to help achieve the spatially balanced development target of the NEP, serving as a means to improve the socioeconomic status of the population in general, and increase the participation of Bumiputras in particular, in the modern urban sector (2nd Malaysia Plan, 1971). Conscious planning which characterizes the country’s development since independence has placed Malaysia currently to be among Asia’s best. The challenge of the concomitant rapid rate of urbanization however, continues to remain one of bridging the multidimensional urban-rural gaps. The National Urbanization Policy (NUP) and National Physical Plan (NPP) while fully cognizant of the potentially divisive globalization effect on national development, stress the enhancement of overall living qualities for sustainability. This paper seeks to explore the differences between the importance and satisfaction in living qualities between the urban and rural dwellers in 14 quality of life domains. These domains are Population and Family, Participation in Education, Human Resource, Health, Income, Expenditures and Savings, Housing, Environment, Transportation, Culture and Entertainment, National Unity, Communication and Technological Change, Social Participation, Public Safety and Social Security. Quality of Life Index in this study which is based on a questionnaire survey on 3,500 respondents was derived using the Customer Satisfaction Index. It revealed a gap between the perceived importance and satisfaction rating for most of the quality of life domains studied. This gap prevailed for both rural and urban respondents.